Clinical mentoring to improve quality of care provided at three NIM-ART facilities: A mixed methods study - Chris A. Visser; Jacqueline E. Wolvaardt; David Cameron; Gert J.O. Marincowitz (AOSIS, 2018)
Background: The South African Department of Health implemented the nurse-initiated management of antiretroviral treatment (NIM-ART) programme as a policy to decentralise services. Increasing access to ART through nurse initiation results in significant consequences. Aim: This study evaluated the quality of care provided, the barriers to the effective rollout of antiretroviral services and the role of a clinical mentor. Setting: The study was conducted at three NIM-ART facilities in South Africa. One clinic provided a high standard of care, one had a high defaulter rate, and at the third clinic, treatment failures were missed, and routine bloods were not collected. Methods: A mixed methods study design was used. Data were collected using patient satisfaction surveys, review of clinical records, facility audits, focus group interviews, field notes and a reflection diary. Results: NIM-ART nurses prescribed rationally and followed antiretroviral guidelines.Mortality rates and loss to follow-up rates were lower than those at the surrounding hospitals, and 91.1% of nurse-monitored patients had an undetectable viral load after a year. The quality of care provided was comparable to doctor-monitored care. The facility audits found recurrent shortages of essential drugs. Patients indicated a high level of satisfaction. Salary challenges, excessive workload, a lack of trained nurses and infrastructural barriers were identified as barriers. On-going mentoring and support by a clinical mentor strengthened each of the facilities, facilitated quality improvement and stimulated health workers to address constraints. Conclusion: Clinical mentors are the key to addressing institutional treatment barriers and ensuring quality of patient care.